HUBUNGAN PENGETAHUAN, DUKUNGAN ORANG TUA, KEPERCAYAAN DAN PAPARAN MEDIA ONLINE TERHADAP PRAKTEK VAKSINASI COVID-19 PADA SISWA SMPN 23 KONAWE SELATAN TAHUN 2021 - Denji Tiansani Akhmalia; La Ode Muhamad Sety; Fifi Nirmala G (Endemis Journal, 2022)
Covid-19 vaccination is the administration of the Covid-19 vaccine which is specifically given in order to actively increase a person's immunity against the covid-19 virus, so that if one day someone is exposed to Covid-19 they will not get sick or only experience mild illness and will not become a source of transmission. This study aims to determine the relationship between knowledge, parental support, trust and media online exposure with the practice of Covid-19 vaccination on students of SMPN 23 Konawe Selatan in 2021. This type of research is analytic using a Cross Sectional approach. The number of samples was 211 people who were selected using the Proportionate Stratified Random Sampling technique. Data collection is done online using the Google Form platform. The statistical test used the chi-square test with the results showing 179 (84.8%) respondents had  vaccinated against Covid-19 while 32 (15.2%) had not vaccinated against Covid-19. The results showed that there was a relationship between parental support (p value = 0.009) and the practice of vaccinating Covid-19 on students of SMPN 23 Konawe Selatan. on the other hand, there is no relationship between knowledge (p value = 0.391), trust (p value = 1,000) and exposure to online media (p value = 0.669) on the practice of Covid-19 vaccination among students of SMPN 23 Konawe Selatan.